Knowledge of official ethical standards and tolerance towards corruption: An exploratory study (Analele Universității din București. Științe Politice, 2025)
Corruption is often defined as a deviant conduct from established legal and formal norms and expected ways of behaving in the exercise of official duties and the discharge of official responsibilities. Readiness to tolerate corruption will hinge primarily upon the evaluator’s understanding of what those ethical standards are. This means that citizens’ willingness to accept corruption as something “normal” to the functioning of democracy or “beneficial” to economic development is likely to be affected by how knowledgeable they are about the ethical standards of governing public office. Such knowledge can be instilled by academic and experiential learning. So, we question to what extent citizens’ knowledge of official ethical standards affect their tolerance towards corruption? Based on new individual level data collected from six focus groups conducted in Portugal, we show a possible negative association between the appropriate knowledge of official ethical standards and tolerance towards corruption. The results are exploratory, but sufficiently interesting to test our hypothesis with a larger sample.